2021
DOI: 10.3389/fimmu.2021.703298
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk Between Intestinal Microbiota Derived Metabolites and Tissues in Allogeneic Hematopoietic Cell Transplantation

Abstract: Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is an evidence based- cellular immunotherapy for hematological malignancies. Immune reactions not only promote graft-versus-tumor effects that kill hematological malignant cells but also graft-versus-host disease (GVHD) that is the primary complication characterized by systemic organ damages consisting of T-cells and antigen presenting cells (APCs) activation. GVHD has long been recognized as an immunological reaction that requires an immunosuppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 175 publications
(204 reference statements)
0
13
0
Order By: Relevance
“…In previous studies, Enterococcus, Streptococcus, and various Proteobacteria were dominant during HSCT. Among them, enterococcal dominance increased vancomycin-resistant Enterococcus bacteremia risk by nine folds, whereas proteobacterial domination increased Gram-negative rod bacteremia risk by five folds [ 13 , 39 ]. Although Enterococcus was not significantly different between the BSI and non-BSI groups in our study, the increased potentially harmful bacteria (especially Enterobacteriaceae reported) and decreased beneficial bacteria under serious disease conditions were proven, and its predictability for BSI was confirmed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, Enterococcus, Streptococcus, and various Proteobacteria were dominant during HSCT. Among them, enterococcal dominance increased vancomycin-resistant Enterococcus bacteremia risk by nine folds, whereas proteobacterial domination increased Gram-negative rod bacteremia risk by five folds [ 13 , 39 ]. Although Enterococcus was not significantly different between the BSI and non-BSI groups in our study, the increased potentially harmful bacteria (especially Enterobacteriaceae reported) and decreased beneficial bacteria under serious disease conditions were proven, and its predictability for BSI was confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggested that HSCT patients with elevated bile acid levels may be related to subsequent BSI onset. Bile acid metabolites could modulate immune cells to regulate host immunity [ 39 , 41 ]. Altered host immunity caused by bile acids might be a possible reason for BSI occurrence in HSCT patients.…”
Section: Discussionmentioning
confidence: 99%
“…HSCT affects the intestinal microbiota, microbiomemetabolome and liver axis which can alter intestinal homeostasis and the severity of GVHD (20) . The use of ursodeoxycholic acid is considered useful in the prophylaxis and treatment of some liver conditions, especially from DECH for being one of the reasons that Rev.…”
Section: Discussionmentioning
confidence: 99%
“…HSCT affects the intestinal microbiota, microbiome-metabolome and liver axis which can alter intestinal homeostasis and the severity of GVHD 20 . The use of ursodeoxycholic acid is considered useful in the prophylaxis and treatment of some liver conditions, especially from DECH for being one of the reasons that may lead to the need for HSCR according to the results presented by this study.…”
Section: Discussionmentioning
confidence: 99%